Mycotic Aneurysm after Bacillus Calmette-Guérin Treatment: Case Report and Review of the Literature. (20th February 2017) - Coddington, Nathaniel D.; Sandberg, Jesse K.; Yang, Chen; Sehn, Jennifer K.; Kim, Eric H.; Strope, Seth A.
Abstract : Background . Intravesicular Bacillus Calmette-Guérin (BCG) is an effective adjunctive therapy for superficial bladder cancer that has been shown to delay recurrence and progression of disease. Serious side effects are relatively rare but are difficult to diagnosis and commonly overlooked. Case Presentation . We report the case of a patient who was found to have mycotic aortic aneurysms secondary to treatment with BCG after a prolonged course with multiple intervening hospitalizations. Conclusion . Through this report, we discuss our present understanding of BCG infection following treatment and review the literature regarding this particular rare manifestation.